COMPARISON OF THREE CHEMOTHERAPY REGIMENS TO THE DECREASE IN LEUKOCYTES AND THE INCIDENCE RATE OF NEUTROPENIA IN PATIENTS WITH NASOPHARYNGEAL CANCER AT DR. HASAN SADIKIN GENERAL HOSPITAL BANDUNG - Afifah, Nadiya Nurul; Pratiwi; Lestari, Keri; Diantini, Ajeng (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Nasopharyngeal cancer is the ninth most common cancer in Indonesia. The death of cancer patients is not only caused by cancer itself, but also several other factors such as the side effects of chemotherapy. Some side effects that occurred are decrease in leukocytes and incidence of neutropenia. Neutropenia is the highest hematological toxicity caused by chemotherapy treatment which has final manifestation is death from systemic infection. The purpose of this study is to compare three chemotherapy regimens in causing a decrease in leukocytes and the incidence of neutropenia in the patients with nasopharyngeal cancer in RSUP. Dr. Hasan Sadikin Bandung. Methods: The three chemotherapy regimens compared in this study are cisplatin, cisplatin/5-fluorouracil (5-FU), and carboplatin/paclitaxel. This research is an analytic observational study with retrospective data collection and cross-sectional analytic design. The data were obtained from the medical records of inpatients with nasopharyngeal cancer during January-December 2015; total data 86 nasopharyngeal carcinoma patient[s] (>18 years old, female and male) data had been analyzed in this study. Results: The percentage of neutropenia incidence in cisplatin regimen is 8.3%, in cisplatin/5-FU is 14.3%, and in carboplatin/ paclitaxel is 18.6%. Conclusion: The results showed that there are no significant differences (p>0.05) in the three regimens in causing the reduction of leukocyte (p=0.327) and the average of absolute neutrophil count (p=0.240).